The influence of audit committee and institutional ownership on earnings management with financial performance as intervening variables - UMMU FITRIANI; ARIFUDDIN; AINI INDRIJAWATI (International Journal of Multidisciplinary Research and Studies, 2023)
This study aims to examine the influence of the Audit Committee and Institutional Ownership on Earnings Management with Financial Performance as Intervening Variables. This study uses a quantitative approach. The population of this research is all manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2018-2021, totaling 220 companies. Sample selection was carried out using purposive sampling method with a final sample of 120 financial reports. The data processing technique used in this study is the Statistical for Social Sciences (SPSS) application version 21. The results of this study indicate that the Audit Committee has a negative effect on Earnings Management, Institutional Ownership has no effect on Earnings Management, the Audit Committee has a positive effect on Financial Performance, Institutional Ownership has a positive effect on Financial Performance, Financial Performance has a positive effect on earnings management, the Audit Committee has an effect on earnings management through Financial Performance, and Institutional Ownership has no effect on Earnings Management through Financial Performance.